Electronic Publishing Programs in Science and Technology Part 1: The Journals - Elizabeth W. Brown; Andrea L. Duda (Issues in Science and Technology Librarianship, 1996)
Many science and technology journal publishers are starting web-based publishing programs. In some cases publishers are making all or most of their journals available; in others, one or two titles are being published on the web as pilot projects. This article summarizes information about programs from several science and technology publishers in a "snapshot" from November 1996. Since many of these publishing programs are currently in development, visit the publishers' web sites for the latest information.